IMPLEMENTASI PENGGUNAAN MEDIA KARTU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK USIA DINI - Astrid Putri Malandi; Novianti Saadah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The importance of using learning media that is appropriate to the developmental characteristics of early childhood, especially in Islamic Religious Education (PAI) learning. Children aged 4–5 years are in the preoperational development stage which is easier to understand concepts through visual media and concrete experiences. However, in practice, PAI learning is often still dominated by verbal methods so that it is less interesting and less optimal in increasing child engagement. Therefore, the use of flashcards is an alternative learning media that can help children understand PAI material in a more interesting and interactive way. This study aims to describe the implementation of the use of flashcards in Islamic Religious Education learning for children aged 4–5 years at Syuhada Kindergarten. The focus of the research includes planning the use of flashcards, implementing the use of flashcards in the learning process, evaluating the use of flashcards, as well as supporting and inhibiting factors in its implementation, including children's responses and involvement during learning activities. This study uses a qualitative approach with a field research type. The research subjects include class teachers of the 4–5 year old age group and the principal of Syuhada Kindergarten as supporting informants. Data collection techniques are carried out through observation, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources and techniques. The results showed that the use of flashcards at Syuhada Kindergarten was planned in the learning program and implemented interactively through games that increased children's activity, enthusiasm, and engagement. Flashcards also helped improve children's understanding and retention of the material, particularly the hijaiyah letters, due to their concrete and engaging nature. Despite challenges in discipline and differences in children's abilities, flashcards were generally effective in creating more engaging, active, and meaningful learning